Therapeutic efficacy of chloroquine and sulfadoxine/pyrimethamine against Plasmodium falciparum infection in Somalia - Warsame M.; Abdillahi A.; Duale O. Nur; Ismail A. Nur; Hassan A. M.; Mohamed A.; Warsame A. (The World Health Organization, 2002)
OBJECTIVE: To assess the efficacy of chloroquine and sulfadoxine/pyrimethamine in the treatment of uncomplicated Plasmodium falciparum infections in Somalia. METHODS: Patients with clinical malaria in Merca, an area of high transmission of the disease, were treated with the standard regimens of chloroquine (25 mg/kg) or sulfadoxine/pyrimethamine (25 mg sulfadoxine and 1.25 mg pyrimethamine per kg). Similar patients in Gabiley, an area of low transmission, received the standard regimen of chloroquine. The clinical and parasitological responses were monitored for 14 days. FINDINGS: Chloroquine treatment resulted in clinical failure in 33% (n = 60) and 51% (n = 49) of the patients in Merca and Gabiley respectively. There were corresponding parasitological failures of 77% RII/RIII and 35% RII/RIII. Patients who experienced clinical failure had significantly higher initial parasitaemia than those in whom there was an adequate clinical response, both in Merca (t = 2.2; P t = 2.8; P n = 50) of the patients achieved an adequate clinical response despite a parasitological failure rate of 76% RII/RIII. CONCLUSION: Chloroquine should no longer be considered adequate for treating clinical falciparum malaria in vulnerable groups in the areas studied. Doubts about the therapeutic life of sulfadoxine/pyrimethamine in relation to malaria are raised by the high levels of resistance in the Merca area and underline the need to identify suitable alternatives.